2020
DOI: 10.1093/rap/rkaa056
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in anti-neutrophil cytoplasmic antibody-associated vasculitis: an underlying prothrombotic condition?

Abstract: Objectives We investigated the incidence and potential underlying risk factors of venous thromboembolism (VTE) in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). We assessed haemostatic disturbances and factors that may contribute to the risk of VTE development. Methods ANCA-positive AAV patients (n = 187) were included. Previously identified risk factors for VTE and current medication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…61% of the VTE episodes in this study occurred within the rst 12 months following diagnosis of AAV where disease activity and in ammation are high. This temporal relationship has also been observed in recent studies suggesting that in ammation and a pro-thrombotic state must be considered (3,4). The majority of the VTE episodes that occurred later in the disease course were around the time of severe infection, malignancy, or relapse of AAV, all of which can be associated with an elevation of in ammation and thus promote thrombosis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…61% of the VTE episodes in this study occurred within the rst 12 months following diagnosis of AAV where disease activity and in ammation are high. This temporal relationship has also been observed in recent studies suggesting that in ammation and a pro-thrombotic state must be considered (3,4). The majority of the VTE episodes that occurred later in the disease course were around the time of severe infection, malignancy, or relapse of AAV, all of which can be associated with an elevation of in ammation and thus promote thrombosis.…”
Section: Discussionsupporting
confidence: 69%
“…Venous thromboembolism (VTE) in patients with AAV is common with previous studies identifying a 4fold increased risk in AAV compared with the general population. Furthermore, VTE adds to the considerable morbidity and mortality within this vulnerable population (3)(4)(5)(6)(7)(8). A number of studies have indicated that the highest risk of VTE occurs during periods of disease activity when in ammation is high, although patients with AAV remain hypercoagulable even during remission (3, 5-7, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) in patients with AAV is common with previous studies identifying a 4-fold increased risk in AAV compared with the general population. Furthermore, VTE adds to the considerable morbidity and mortality within this vulnerable population [ 3 8 ]. A number of studies have indicated that the highest risk of VTE occurs during periods of disease activity when inflammation is high, although patients with AAV remain hypercoagulable even during remission [ 3 , 5 – 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VTE adds to the considerable morbidity and mortality within this vulnerable population [ 3 8 ]. A number of studies have indicated that the highest risk of VTE occurs during periods of disease activity when inflammation is high, although patients with AAV remain hypercoagulable even during remission [ 3 , 5 – 7 , 9 , 10 ]. Several mechanisms have been described to explain this thrombotic tendency associated with AAV.…”
Section: Introductionmentioning
confidence: 99%
“…The AAV diagnostic groups were divided into subgroups (GPA, MPA,and EGPA) according to the European Medicines Agency (EMEA) algorithm, and all were ANCA positive at the time of diagnosis [ 14 ]. The data collection and the cohort have been described in a previous publication [ 15 ]. For the present study, additional exclusion criteria were added: insufficient knowledge of and inability to read and understand written Swedish.…”
Section: Methodsmentioning
confidence: 99%